Observing Heterogeneous Unsaturated Flow at the Hillslope Scale Using Time‐Lapse Electrical Resistivity Tomography - Kotikian, M. (2020)
Understanding water partitioning and storage on mountain hillslopes is important for vadose zone hydrologic modeling, water balance calculations, and predicting landslides. Revealing the dynamics of unsaturated water movement through time remains challenging due to the scarcity of spatially continuous observations at dense time sampling intervals. We investigate heterogeneous vertical flow using time‐lapse electrical resistivity tomography over a span of 2 yr and use seismic refraction to determine the bedrock location on a hillslope with snow‐dominated hydrology. We expect that heterogeneities in vertical unsaturated flow are driven by highly conductive zones in soil structure and higher localized water content due to surface topographic depressions and a long‐term sustained snowpack relative to other locations, resulting in increased water availability. The results show that vertical flow heterogeneity and partitioning to deep flow occurred under contrasting precipitation inputs. We determine that topographic and vegetation cover heterogeneities on the hillslope and snow accumulation exert control on the location of partitioning to deep flow, likely due to macropores, roots, boulders, and localized water availability. We conclude that the regolith–bedrock boundary has a slope reversal that allows water to accumulate to drive heterogeneous flow.